Potential Development of Sharia Tourism at Cheng Ho Mosque, Purbalingga - Suryandari, Sofia Yustiani; Listiani, Fitri (Jurnal Indonesia Sosial Sains, 2025)
This article discusses the development of smart tourism in Purbalingga Regency, focusing on the Cheng Ho Mosque as the main destination. Smart tourism, which uses information and communication technology (ICT), aims to improve the tourist experience and the efficiency of tourism management. This research uses qualitative methods through observing, interviewing, and documenting to understand the potential and challenges of developing Sharia Tourism at Cheng Ho Mosque. Although it has bright prospects with government support, challenges such as limited human and financial resources and lack of collaboration among stakeholders still exist. Cheng Ho Mosque, which combines Chinese and Islamic cultures, offers worship facilities and educational tours but needs improvement in promotion and management. This study recommends increased government support, training of tourism managers, and the use of digital technology to increase tourist attraction.